FOCUS OF VISCERAL LEISHMANIASIS IN DISTRICT ABBOTTABAD - Mannan, Modood ul; Yousaf, Muhammad; Idrees, Muhammad; Babur, Ghufran Saeed (Journal of Ayub Medical College Abbottabad, 2000)
Background: A lot of studies are available regarding geographical distribution of leishmaniasis in Pakistan. We report our experience in Abbottabad district. Results: We have diagnosed 35 cases of visceral leishmaniasis by bone marrow aspirate examination in the Department of Pathology, Ayub Medical College, Abbottabad, during the period from January 1992 to December 1996. All the cases belonged to Hazara Division. Twenty-four cases (68.5%) belonged to an area of 5 km radius located about 15 kms from Abbottabad. This main area comprises the villages of Dhamtor, Azizabad, Bagh Bandi, Nathiagali and Berangali. In our study, it is this strip which is the focus of the disease in District Abbottabad. Further epidemiological studies are required to complete the picture of various types of Leishmaniasis and its distribution in this area.